Development and characterization of 20 polymorphic microsatellite markers for Livistona chinensis R. Br. var. subglobosa Becc., a fan palm in the Ryukyu Archipelago, Japan. Issue 4 (5th May 2017) - Kondo, Toshiaki; Kajita, Rie; Yamada, Toshihiro
Abstract : Livistona chinensis R. Br. var. subglobosa Becc. is a subtropical fan palm distributed mainly in the islands of the Ryukyu Archipelago, Japan. Some small populations, separated by a few 100 km from the main species range, are also established on islands around northern Kyushu and Cape Ashizuri, Shikoku. Most of those are designated as national or prefectural natural treasures. We developed 20 microsatellite markers for this species and characterized them for polymorphisms within six populations. The number of alleles per locus ranged from two to nine, with an average of 4.2; the expected heterozygosity ranged from 0.16 to 0.61, with an average of 0.46. These markers will be useful for investigating disjunct range formation within L. chinensis var. subglobosa and the origins of the remote populations, providing crucial information for conservation of the populations. Abstract : Livistona chinensis R. Br. var. subglobosa Becc. is a subtropical fan palm distributed mainly in the islands of the Ryukyu Archipelago, Japan. We developed 20 microsatellite markers for this species and characterized them for polymorphisms within six populations.